Respuesta :
f(x) = x + 4
g(x) = -2x^2 + 3x - 1
(f - g)(x) = f(x) - g(x) = x + 4 - (-2x^2 + 3x - 1) = x + 4 + 2x^2 - 3x + 1 = 2x^2 - 2x + 5
g(x) = -2x^2 + 3x - 1
(f - g)(x) = f(x) - g(x) = x + 4 - (-2x^2 + 3x - 1) = x + 4 + 2x^2 - 3x + 1 = 2x^2 - 2x + 5
Answer:
[tex]2x^2-2x+5[/tex]
Step-by-step explanation:
Given,
[tex]f(x)=x+4[/tex]
[tex]g(x)=-2x^2+3x-1[/tex]
[tex](f-g)(x)=f(x)-g(x)[/tex] ( Subtraction of two functions )
[tex]=(x+4)-(-2x^2+3x-1)[/tex] ( By substituting values )
[tex]=x+4+2x^2-3x+1[/tex] ( Distributive property )
[tex]=2x^2-2x+5[/tex] ( Combining like terms )
Hence,
[tex](f-g)(x)=2x^2-2x+5[/tex]
Option d is correct.